HUBUNGAN KELOMPOK ACUAN, PERCEIVED VALUE, PERCEIVED QUALITY DAN MEDIA SOSIAL TERHADAP NIAT PEMBELIAN SERTA DAMPAKNYA PADA KEPUTUSAN PEMBELIAN SEPEDA PUSHBIKE (STUDI PADA KOMUNITAS PUSHBIKE SURABAYA) - Novelia Asita Mranani; Siwidyah Desi Lastianti (STIE Mahardhika, 2022)
In line with the development of the business world today, the level of competition in meeting human needs is increasing. Reference groups can generate purchase intentions in consumers towards a product. Likewise with perceived value and perceived quality. Perceived value is an important thing, because if a product is not able to produce value for the product. A company is also supported by producing quality products or having perceived quality that is truly in accordance with its functions and uses, or even has the advantage of a product that is the same as expected by consumers. Information search and ease of use of social media is the most important stage for decision making in shopping on social media. Before consumers make a purchase, usually they will look for information about the desired product or the product being offered by the manufacturer. The purpose of this study was to analyze the influence of reference groups, perceived value, perceived quality and social media on purchase intention. As well as to analyze the effect of purchase intentions on purchasing decisions. The sample of this research is members of the Surabaya Pushbike community, with a total sample of 100 respondents. The analysis technique uses SEM (Structure Equation Model) with PLS (Partial Least Square) program or software. The results showed that of the 9 hypotheses all had a positive and significant effect, there were only 3 hypotheses that had no positive and significant effect. Among other things, perceived value does not have a positive and significant effect on purchase intentions, the reference group does not have a positive effect on purchasing decisions, and social media does not have a positive effect on purchasing decisions.